Na parada do lazer: diagnóstico do campo de atuação profissional nas ONGs LGBT de Belo Horizonte/MG - Marie Luce Tavares (2011)
The Movement of Lesbians, Gay, Bisexual and Transgender (LGBT) in Brazil has been consolidating since the 1970s, characterized as a manifestation for the right to freedom of sexual orientation. In 90 years, there is a revival in homosexual militancy, with increasing the number of institutionalized groups, spread across the country. The emergence of these organizations is characterized by the pursuit of autonomy against the State, leading the movement to settle from the model of Nongovernmental Organizations (NGOs) that fall within the named "third sector". The incorporation of social management demanded professionalization, aimed maintaining of the quality of services and systematization of actions. Being one of the leisure areas of service to communities and social organizations, we can imply the need to professionalization of the area. In this context, the proposed study objective to diagnose and analyze the field of professional activity in the recreation sector in the third, in order to understand the work performed in this field for Non-Governmental Organizations related to the LGBT movement. For that, I try to analyze the concepts of recreation that pervades the actions of these organizations, to diagnose the actions directly or indirectly related to recreation, to identify the individuals responsible and working with these actions and understand the "role" of these professionals in the organization and development these actions. Therefore, I present how the proposed methodology bibliographic research combined with the documentary and field survey, applying the immersion in the field and semi-structured interviews as data collection instruments. We analyzed two institutions located in Belo Horizonte / MG, through interviews with six professionals working within the recreation. I emphasize that there is not necessarily a specific professional involved in the planning, implementation and evaluation of these activities. However, there is a certain approach and greater involvement of some people ahead of organizing such activities. The actions of play are directed to meet the LGBT audience, but there is openness to other persons. The goals of these actions vary, fitting them since the work of self-esteem to the empowerment of the public seeking its social protagonism. There are a variety of actions that involve the several contents of recreation, arts, physical activities. In relation to the professionals involved, the relationship established with the institution is the militancy activities and actions results, in most cases, voluntary work. Regarding the profile of these professionals, it emphasizes the importance of knowing the reality, when working with the LGBT audience, as well as mastery of content but there is a need for more clarity about the knowledge in the leisure and culture. The concepts of recreation present in a diverse, converging in their understanding as a time characterized by a seeks of pleasure, but which has no relation to the requirements. Regarding the presence of recreation on the agenda of the LGBT movement, I believe that there is clarity on the part of respondents on this issue, but despite being embedded in the actions of institutions, leisure is not envisioned as the same priority. Therefore, this work presents some challenges that invite you to think about the field of practice in recreation in LGBT NGOs, participatory planning of actions, use and appropriation of public spaces for recreation, investment in the sector, and awareness of leisure as a right. Considering all the analysis, I point out a perspective for the work within these institutions of Leisure Cultural Animation, from an educational proposal based on the idea of mediation, with the intention of provoking questions about the established social order and contribute to overcoming the status quo.